Pengetahuan dan Self -Management dengan Pencegahan Komplikasi Diabetes Melitus (STIKes Surya Global Yogyakarta, 2023)
Background: The number of people with diabetes mellitus in the world reached 425 million aged 20-79 years in 2017. The high number of people with diabetes mellitus is caused by a low level of knowledge and awareness in early detection of diabetes mellitus which is not good. Based on data from the top 10 diseases at Mergangsan Health Center on October 2021, it shows that diabetes mellitus is included in the top 10 diseases in 3rd place, namely Type 2 Diabetes Mellitus Non-Insulin-Dependent as many as 894 people .Methods: This study used quantitative methods. The research samples were 80 people with diabetes mellitus without complications of diabetes mellitus. The data collection technique used purposive sampling. The instrument used for data collection was the DKQ (Diabetes Knowledge Questionnaire) and DSMQ (Diabetes Self Management Questionnaire) questionnaires. Analysis of data processing using Chi Square Test and the research design is cross sectional.Results: Based on the results of the Chi-Square test, the knowledge variable with the degree of error used = 0.05 and n = 80, it can be assessed with a significant p-value of 0.025. The results showed that the p value of 0.05 means that Ha was accepted and Ho was rejected, which means that there was a correlation between the knowledge variable and the prevention of diabetes mellitus complications and the diabetes mellitus self-management variable, with a significant p-value of 0.000. These results indicated that a p-value of 0.05 means Ha was accepted and Ho was rejected, which means that there was a correlation between the self-management variable and the prevention of complications of diabetes mellitus.Conclusion: There is a significant correlation between knowledge and self-management of diabetes mellitus with the prevention of complications of diabetes mellitus at Mergangsan Health Center, Yogyakarta City.